Exposure to violent video and aggressive behavior among Public Secondary Students, Kwara State, Nigeria - Ajiboye, Samuel Kolawole; Esorun, Oluwatoni; Oladejo, Bolaji (Humanitas: Indonesian Psychological Journal, 2024)
Aggressive behavior is a range of acts that result in physical and psychological harm to the perpetrator, and other students, thus hindering learning activities. This study investigated the relationship between exposure to violent videos and aggressive behavior among public secondary students in Kwara State, Nigeria. The survey method with a correlational design was adopted. A total sample of 381 participants was involved using the stratified random sampling technique. A research-designed questionnaire titled Exposure to Violent Videos and Aggressive Behaviour Questionnaire (EVABQ) was used to collect the data. Pearson’s product-moment correlation and t-test statistics were used to analyze the hypotheses. Results revealed a positive relationship between exposure to violent videos and aggressive behavior. The results showed statistically significant differences in exposure to violent videos and aggressive behavior among public secondary students based on gender and age. Male respondents were more exposed to violent videos and had more aggressive behavior than females. In contrast, students below 15 years old were more exposed to violent videos and exhibited aggressive behavior than 15 years and above. Therefore, school counselors should sensitize public secondary students to the influence of exposure to violent videos on aggressive behavior, especially among males and students below 15 years old.